Addressing challenges in sealing of scalable multifiber module for O-2 enrichment using LSCF membranes - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (International Journal of Applied Ceramic Technology, 2022)
Scalable and multifiber modules in oxygen separation face huge challenges due to difficulty in integrating all the necessary components, especially in sealing the fibers in a gas tight module. Here, we report our findings on design and fabrication of a multifiber La0.6Sr0.4Co0.2Fe0.8O3-delta (LSCF)-based module, which can be scaled up. The focus is on sealing ceramic-metal interfaces by layering of sealants of varying thermal properties. We have also incorporated the use of dead ended fibers to minimize ceramic-metal interfaces in the hot zones and present a new method for dead ending by flame melting. Pressurizing the air inlet feed from either bore side or shell side is detrimental to the structural integrity of the fibers. A thorough characterization of the fresh and spent fibers is also carried out using X-ray tomography and electron microscopy, which indicates effect of temperature and pressure on the fibers.
Keywords: Characterization; permeability; Perovskites

Understanding the structural characteristics of modified ceramic hollow fiber oxygen transport membranes through in silico tomography simulation study - Jogdand, Shunottara M.; Sharma, Jyoti; Khilari, Rushikesh S.; Mahajan, Digvijay P.; Patil, Prashant; Pol, Harshavardhan V.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2025)
Design and development of integrated membrane reactor systems are gaining attention as a sustainable solution capable of performing multiple functions in a single reactor. Membrane reactors made of mixed ionic-electronic conduction materials dosing pure O to the reactions can be exploited for various catalytic processes. In this case, micro- and macrostructures of the membrane surface play a significant role in the permeation performance of membranes, and understanding these parameters prior to scaling up to modules is imperative. Here, 3D X-ray tomography imaging, a versatile nondestructive instrumental technique, is used in understanding the structural behavior of the membrane walls at different structural alignments, leading to anticipation of fouling areas upon assembling membrane reactors. La0.6Sr0.4Co0.2Fe0.8O3-delta hollow fiber membranes are fabricated by the phase inversion method and further modified by the optimized acid etching technique. In silico simulations on different morphologies before and after surface modifications are carried out under varying flow rates at nonambient temperatures to mimic real experimental conditions. Critical parameters such as gas velocity, pressure exerted on cavity walls, and strain, dictating structural integrity of the fibers under experimental conditions, were evaluated. As a result of the assessment, the surface-modified structural morphology with finger-like cavities initiating from the inner wall of the membrane was found to be robust. Increase in the pore size, nonuniform pore size distribution, and irregular and interdigitated cavities formed in outer fingered membranes after multiple surface treatments led to an similar to 5 fold increase in the average pressure exerted at the cavity walls when compared to inner fingered membranes. Strain profile generated for inner fingered membranes shows homogeneous distribution of strain for the applied stress throughout the 3D geometry of the membrane. This detailed structural analysis of the membrane will help in building a more robust and efficient system for scale-up applications.
Keywords: 3D X-ray tomography; in silico simulation; oxygen transport membranes; perovskite; phase inversionmethod